IMPROVING STUDENT ACTIVITIES AND LEARNING OUTCOMES IN CLASS III SDN 021 LADA USANG THROUGH LEARNING ASSOCIATION APPROACH USING LEARNING VIDEOS - Arni Delita (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research is motivated by teacher-centered learning activities and the low student learning outcomes. This research was expected to improve student learning activities and outcomes. This research was a classroom action research on class III students of SDN 021 Lada Usang, involving 13 students. The research was conducted from September to October 2019. The instrument used in this study was the observation sheet of student activities and student learning outcomes tests. The results of this research showed that student activity in the first cycle was 61%, categorized as active, and increased in the second cycle to 83%, which is categorized as very active. The average learning outcomes of students in the first cycle was 74.34 with a classical completeness of 69%, while in cycle II, it increased to 80.38 with a classical completeness of 84%, which is included in the excellent category. Based on the results of this study, it can be concluded that the scientific approach, with the help of instructional video media, can improve student learning activities and outcomes.